Investigation on the transmission of some Tobamoviruses by pollen and seed in pepper (Capsicum annuum L.) - Salamon, P.; Kaszta, M. (International Journal of Horticultural Science, 2000)
Five pepper cultivars were mechanically inoculated with isolates of three Tobamovirus species, viz. the "Gelb" strain of tobacco mosaic virus (TMV-G), the XM-isolate of dulcamara yellow fleck virus (DYFV-XM) and the Nov/H isolate of pepper mild mottle virus (PMMV-Nov/H), respectively. Symptoms caused by the viruses were characterised. The viruses were sucessfully re-isolated from different organs (roots, leaves, fruit parts) of susceptible peppers to test plants. It was estabilished, that the pollen of diseased peppers carried infective virions at least on their surface. Washes of seeds were highly infective, but no infectivity was found after treatment of the seeds with 2% NaOH or 10% Na3PO4. No infectivity of inocula prepared from seed-coats of alkaline treated seeds was established. Infection of young seedlings grown from untreated seeds was demonstrated, while the seedlings came from alkaline treated seeds remained free of infective virus. The possible role of pollen and seed in the epidemiology of Tobamoviruses pathogenic to pepper as well as the importance of seed treatment is discussed.